Revisiting the organization of independent work of students under the supervision of a teacher (IWST) - Zhetpisbayeva, B.A.; Bencic, S.; Zhilbayev, Zh.O.; Baideldinova, G.M. (Publ.KarSU, 2017)
This article is devoted to the issues of organizing independent work of students under the supervision of a teacher in higher educational institutions. The article deals with such concepts as «independent work of students », as well as «independent work of students under the supervision of a teacher» and «cognitive independence ». The authors analyzed the works of domestic and foreign researchers on the definition and forms of organization of independent work of students under the supervision of a teacher that showed that the definition of the IWST is treated ambiguously. The article also presents the results of a questionnaire survey of teachers and students of the Karaganda State University named after Academician E.A. Buketov to determine the current situation on the organization of the IWST on a foreign language, namely, to determine the role of this type of classroom activities in the educational process, the forms of its organization, the difference of these forms from the forms of organization of other types of occupations. To clarify the essence of the IWST concept, the authors also considered the characteristics of the IWS, which led to the conclusion that the classification of the types of independent work of a student under the supervision of a teacher depends on the pedagogical goal, the nature of the student's activity, the degree of independence, and also on the specifics of the academic subject.
Оқытушының жетекшілігімен студенттердің өздік жұмысын ұйымдастыру туралы
К вопросу об организации самостоятельной работы студентов под руководством преподавателя (СРСП)
Keywords: credit system; higher education; independent work of students; university; interaction between teacher and student; foreign language; cognitive independence; formation of skills; improvement; forms of organization; survey; motivation